The Effect of Giving Honey Pineapple Juice on Decline Cholesterol Levels - Yusiana Vidhiastutik; Karisma Dwi Ana; Eliza Zihni Zatihulwani (Adi Husada Nursing Journal, 2025)
Eating excessive foods high in fat and cholesterol can increase cholesterol levels and can cause various risk dangerous in Health. Lifestyle No controlled and uncontrolled healthy can also cause disease cholesterol . Non- pharmacological treatment For lower level cholesterol that is not cause effect beside one of them with giving honey pineapple juice. The objective of this study is to determine the effect of giving honey pineapple juice on reducing cholesterol levels in Bedali Village, RW 11 Lawang, Malang. This research method uses a quantitative method with a pre-experimental one-group pretest- posttest design. The population in this study were all cholesterol sufferers in Bedali Village, RW 11, Lawang, Malang. The sample in this study consisted of 32 respondents selected using a purposive sampling technique. The results of the study showed that before giving honey pineapple juice to 32 respondents, almost all respondents, 24 respondents (75%) had high cholesterol levels, after giving honey pineapple juice for 7 days, almost all respondents, 28 respondents (87.5%) had normal cholesterol levels, and based on the Wilcoxon Test, the asymp. Sig. (-2 tailed) value was .000 or P-Value (<0.05). Honey pineapple juice can have a positive impact on reducing cholesterol levels, making it a non-pharmacological therapy for managing cholesterol levels. This study shows a significant decrease due to the administration of honey pineapple juice to cholesterol sufferers without involving the consumption of pharmacological drugs.